SEM evaluation of contamination of dentinal tubules in open apex teeth treated with MTA plug - Behnaz Barekatain; Ali Reza Farhad; Maryam Zolfaghari (Isfahan University of Medical Sciences, 2011)
Introduction: Generally, the root canal walls become contaminated with MTA during MTA plug placement. On the other hand, the dentinal tubules need to be open for penetration of sealer. The aim of this study was to compare dentinal tubule contamination during MTA apexification between one-visit and two-visit appointments. Materials and methods: In this in vitro experimental study, 38 single-canal human teeth, consisting of two groups of 17 and one control group of 4, were placed in 5.25% NaOCl for 30 minutes. The tooth crowns were removed at CEJ; then 2 mm of root ends were cut to create open-apex roots. Canal preparation and shaping were performed up to file #100 and Gates Gliden drill #4 using the step-back technique. The smear layer was removed using NaOCl and EDTA. Finally, the canals were dried. In groups one and two, MTA plug was condensed at root end at a thickness of 3 mm. In group one (one-visit), the samples were prepared for SEM immediately after cleaning the canal walls. In group two (two-visit), the samples were kept under 100% humidity at 37ºC in an incubator for 24 hours. Then, the canals were irrigated with ultrasonic and 2.5% NaOCl and prepared for SEM. In the control group, only the smear layer was removed and the samples were prepared for SEM without MTA plug. Mann-Whitney and Kruskal-Wallis statistical tests were used for statistical analysis (α=0.05). Results: There was a significant difference between the groups in relation to contamination of the dentinal tubules with significantly more MTA on the canal walls in group one compared to group two (p value < 0.001). The dentinal tubules were completely open in the control group. Conclusion: The results of this study showed that in apexification with MTA in open apex teeth, two-visit treatment sessions are superior to one-visit sessions. Key words: Apexification, MTA, Root canal therapy, Scanning electron microscopy.